2018
DOI: 10.2903/j.efsa.2018.5389
|View full text |Cite
|
Sign up to set email alerts
|

Peer review of the pesticide risk assessment of the active substance clopyralid

Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Finland, and co-rapporteur Member State, Poland, for the pesticide active substance clopyralid are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of clopyralid as a herbicide on winter cereals and grasslan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 3 publications
0
35
0
Order By: Relevance
“…From the rotational crop metabolism studies which were assessed in the framework of the EU pesticides peer review, it was concluded that the same metabolic pattern is observed across all rotational crops and that this corresponds with the findings in primary crops with clopyralid and conjugated clopyralid being the major residues (EFSA, 2018d). The studies covered three plant back intervals (PBI), with quantifiable amounts reported at PBI of 30 days (except for radish roots) and identification performed in all plant parts.…”
Section: Residues In Plantsmentioning
confidence: 55%
See 4 more Smart Citations
“…From the rotational crop metabolism studies which were assessed in the framework of the EU pesticides peer review, it was concluded that the same metabolic pattern is observed across all rotational crops and that this corresponds with the findings in primary crops with clopyralid and conjugated clopyralid being the major residues (EFSA, 2018d). The studies covered three plant back intervals (PBI), with quantifiable amounts reported at PBI of 30 days (except for radish roots) and identification performed in all plant parts.…”
Section: Residues In Plantsmentioning
confidence: 55%
“…The metabolism of clopyralid in primary crops belonging to the group of root crops (sugar beets), leafy crops (head cabbage), pulses/oilseeds (oilseed rape) has been investigated in the framework of the previous MRL application and EU pesticides peer review (EFSA, 2011, 2018d). In the context of the peer review, a data gap was identified for the clarification of the unknown polar compound observed in mature samples of rape seed and sugar beet.…”
Section: Residues In Plantsmentioning
confidence: 99%
See 3 more Smart Citations